2020
DOI: 10.1002/pat.5001
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale analysis on multiextruded poly(lactic acid)/organoclay nanocomposites: Insights into the underlying mechanisms of thermomechanical degradation

Abstract: Due to the growing market and the relatively high price of poly(lactic acid) (PLA), the possibility to recycle PLA has attracted a tremendous attention, aiming to reduce the environmental impact related to the life cycle of PLA-based products. However, the comprehensive structural and properties changes of PLA and PLA/clay nanocomposites induced by reprocessing are still not clear. In this work, PLA and its organoclay nanocomposites (PCN5) were subjected to repeated extrusion for 1 and 4 cycles to reveal their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Additionally, Meng et al [38] reported a decrease in M n and M w , from 92.6 kg/mol and 112 kg/mol to 83.8 kg/mol and 104 kg/mol, respectively. Other researchers [5,12,17,20,[28][29][30]43,[49][50][51][52][53][54][55][56][57][58][59] reported the same decreasing trend in molecular weight, which makes M n and M w good indicators to monitor process-induced degradation. Whether the decrease is small or large depends on the selected processing technique and parameters, as will be further discussed in Section 4.…”
Section: Molecular Weight Distributionmentioning
confidence: 80%
See 2 more Smart Citations
“…Additionally, Meng et al [38] reported a decrease in M n and M w , from 92.6 kg/mol and 112 kg/mol to 83.8 kg/mol and 104 kg/mol, respectively. Other researchers [5,12,17,20,[28][29][30]43,[49][50][51][52][53][54][55][56][57][58][59] reported the same decreasing trend in molecular weight, which makes M n and M w good indicators to monitor process-induced degradation. Whether the decrease is small or large depends on the selected processing technique and parameters, as will be further discussed in Section 4.…”
Section: Molecular Weight Distributionmentioning
confidence: 80%
“…Benvenuta-Tapia and Vivaldo-Lima [17], Jain et al [54], and Tesfaye et al [28] also reported an increase in the Ð due to degradation, but no clear explanation was given. In the work of Lv et al [52], a Ð decrease was reported from 1.95 for unprocessed PLA to 1.83 after 4 reprocessing cycles, which is explained by the degradation occurring mainly in the chains with a high molecular weight. Amini Moghaddam et al [49] also reported a decrease in Ð, but no explanation was given.…”
Section: Molecular Weight Distributionmentioning
confidence: 94%
See 1 more Smart Citation
“…4 It is widely used in fabricating food garbage bags, medical parts, and disposable containers and exhibits considerable potential for green packaging applications. 5,6 Nevertheless, its rather high brittleness, 7 low-heat distortion temperature, 5 low-biodegradability rate, 8 and high cost could be listed as limitations of PLA in comparison to other biodegradable polymers. 9 One of the key strategies frequently reported in the literature is to blend PLA with soft biodegradable polymers using coupling agents and plasticizers as seen in the binary and trinary polymer blend systems to modify its flexibility, thermal stability, toughness, and degradation rate.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their high surface area and cation exchange, as well as their excellent mechanical properties and thermal resistance, MMT have been an effective filler for differentpolymer matrices, from rubbers 12 to synthetic polymers, such as polystyrene, 13 biopolymers, as polylactide 14 and starch, 15,16 as well as polymer blends 17,18 . It has been reported that the incorporation of a low level of MMT into polymer matrices can significantly improve a large number of physical properties of the virgin polymer, including mechanical and barrier properties, thermal stability, flammability resistance and degradability of biodegradable polymers 19–21 .…”
Section: Introductionmentioning
confidence: 99%